Control of Salmonella Enteritidis on food contact surfaces with bacteriophage PVP-SE2 - Milho, Catarina (2018)
Salmonella is one of the worldwide leading foodborne pathogens responsible for illnesses and hospitalizations, and its capacity to form biofilms is one of its many virulence factors. This work evaluated (bacterio)phage control of adhered and biofilm cells of Salmonella Enteritidis on three different substrata at refrigerated and room temperatures, and also a preventive approach in poultry skin. PVP-SE2 phage was efficient in reducing both 24- and 48-h old Salmonella biofilms from polystyrene and stainless steel causing 2 to 5 log CFU cm2 reductions with a higher killing efficiency at room temperature. PVP-SE2 phage application on poultry skins reduced levels of Salmonella. Freezing phage-pretreated poultry skin samples had no influence on the viability of phage PVP-SE2 and their in vitro contamination with S. Enteritidis provided evidence that phages prevented their further growth. Although not all conditions favor phage treatment, this study endorses their use to prevent and control foodborne pathogen colonization of surfaces.